The meaning of environmental security : ecological politics and policy in the new security era - Barnett, Jon (New York : Zed Books, 2001)
A comprehensive critical discussion of environmental security. It reviews the origins and implications of a variety of approaches. Here Barnett argues that environmental security is often driven more by the power of the security-makers than by the need to address environmental problems.
Includes bibliographical references (p. 161-176) and index.
oif 04/08/16
Loan
Keywords: Environmental policy; Environmental protection; Global environmental change; Sustainable development